NILAI-NILAI KESETARAAN RAS DALAM AL-QUR’AN (KAJIAN ATAS TAFSIR AL-MISBAH) - Huda, Nurul; Islamiyah, Wildatul (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
The purpose of this study is to describe verses related to the values of racial equality, which should be used as